2007
DOI: 10.1097/01.hp.0000258918.36430.a3
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Clinical Rf Hyperthermia on Protection Limits in the Rf Range

Abstract: The systemic temperature is meticulously regulated to 37-37.5 degrees C. Organ systems (skin, digestive system, muscles) have a considerable potential to regulate the perfusion for thermal regulation, physical activity, or digestion. While the regulation of the systemic temperature (37.5 degrees C) is quite strict, the tolerance and regulation potential with respect to local heat is more variable. Laboratory studies provided the relationship between thermal doses and cytotoxic effects. Tissue damage for short-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…WBH represents the most invasive hyperthermia application, requires a great deal of expenditure and bears the risk of severe toxicity when chemotherapeutic agents are applied [3]. In addition to thermal injuries, cardiovascular stress, rise in cardiac index and decrease of systemic vascular resistance are major problems in WBH [7,10]. Whole-body hyperthermia is associated with profound cardio-vascular alterations [10], such as tachycardia and a decrease of mean arterial blood pressure [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…WBH represents the most invasive hyperthermia application, requires a great deal of expenditure and bears the risk of severe toxicity when chemotherapeutic agents are applied [3]. In addition to thermal injuries, cardiovascular stress, rise in cardiac index and decrease of systemic vascular resistance are major problems in WBH [7,10]. Whole-body hyperthermia is associated with profound cardio-vascular alterations [10], such as tachycardia and a decrease of mean arterial blood pressure [6].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to thermal injuries, cardiovascular stress, rise in cardiac index and decrease of systemic vascular resistance are major problems in WBH [7,10]. Whole-body hyperthermia is associated with profound cardio-vascular alterations [10], such as tachycardia and a decrease of mean arterial blood pressure [6]. Furthermore, evaluation of hemodynamic changes during WBH treatment using TEE showed characteristic signs of a hyperdynamic circulation.…”
Section: Discussionmentioning
confidence: 99%
“…These concentrations of SWCNTs far exceeded those used in the earlier RF hyperthermia studies [Gannon et al, 2007]. Ideally, hyperthermia using external RF fields requires local conductivities 25-50 times greater than normal tissue to achieve SARs of 100-200 W/kg at the target while sparing healthy tissue [Wust et al, 2007]. Although these SARs may be achievable at the nanoscopic scale using conductive nanoparticles, it is unclear if they can be achieved at the macroscopic scale through increases in the bulk conductivity of the colloid.…”
Section: Introductionmentioning
confidence: 95%
“…3,7,8 Chondrolysis has also been reported but would appear to relate to higher temperatures in the region of 55 C. 4 Several cadaveric studies in the laboratory have shown that prolonged continuous use of the RF ablation wand without constant fluid flow can result in dangerously high temperatures of greater than 80 Celsius ( C). Much lower temperatures of less than 40 C were witnessed with intermittent use of the RF ablation wand and continuous flow of fluid.…”
mentioning
confidence: 99%